The Implementation of Project-Based Learning Assisted by Canva to Improve Students’ Collaboration and Communication Skills - Ni Made Rusmawati; Sunarto Amus; Hasdin (Institute of Educational, Research, and Community Service)
This study aims to describe the implementation of the Project-Based Learning (PjBL) model assisted by Canva in improving students’ collaboration and communication skills in the Civics Education (PPKn) subject at SMP Negeri 1 Bungku Timur. The background of this research is based on the low level of students’ active participation in the learning process, particularly in aspects of group work and expressing opinions. This research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects were 24 seventh-grade students of class VII B. The results showed that the implementation of the Project-Based Learning model assisted by Canva proved effective in enhancing students’ collaboration skills. This was reflected in students’ active involvement in group task division, discussion, and joint project completion. Students demonstrated positive development in terms of participation, mutual assistance, and responsibility for their respective tasks. The learning process that emphasized teamwork fostered a more open, communicative, and supportive learning environment. In addition, the PjBL model assisted by Canva was also able to improve students’ communication skills. Students became more confident in expressing opinions, using proper and polite language, and presenting project results clearly and structurally. The learning process involving the use of Canva provided students with a creative space to organize ideas visually, making it easier for them to convey messages to the audience. This indicates that the integration of technology into learning can significantly support the development of students’ communication skills. Keywords: Project-Based Learning, Canva, Collaboration, Communication, Civic Education.